The Anthem companion to Hannah Arendt - Baehr, Peter 1935- HerausgeberIn; Walsh, Philip 1965- HerausgeberIn (Anthem companions to sociology, 2017)
"The Anthem Companion to Hannah Arendt offers a unique collection of essays on one of the twentieth century's greatest thinkers. Consisting of a substantial introduction and nine chapters, the companion encompasses Arendt's major works -- The Origins of Totalitarianism, The Human Condition, Eichmann in Jerusalem, On Revolution and The Life of the Mind -- and most salient arguments. The volume also examines Arendt's intellectual relationships with Max Weber, Karl Mannheim, David Riesman and other sociologists. Although written principally for students new to Arendt's work, The Anthem Companion to Hannah Arendt is weighty enough to engage the avid Arendt scholar."--